2001
DOI: 10.1002/1521-3773(20010401)40:7<1305::aid-anie1305>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Power of Protonated Hydrogen Peroxide

Abstract: A simple hydride‐transfer mechanism to produce alkyl cations occurs when isolated protonated hydrogen peroxide (HOOH2+) attacks the C−H bonds of alkanes (except methane) [Eq. (1)]. The chemical properties of HOOH2+, which may serve as a model of the central catalytic motif of key biological systems, have been studied for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Uggerud and co-workers have used CH 4 chemical ionization on H 2 O 2 to generate protonated hydrogen peroxide, HOOH 2 ϩ . The unimolecular and bimolecular reactivity of HOOH 2 ϩ was studied using a sector instrument (EBEB) and an FT-ICR apparatus 225. Metastable HOOH 2 ϩ ions having internal energy sufficiently close to the dissociation threshold decompose spontaneously to form H 3 O ϩ and 3 O, consistent with previous theoretical predictions that ground state singlet HOOH 2 ϩ will decompose with loss of an oxygen atom via a spin change mechanism.…”
supporting
confidence: 76%
“…Uggerud and co-workers have used CH 4 chemical ionization on H 2 O 2 to generate protonated hydrogen peroxide, HOOH 2 ϩ . The unimolecular and bimolecular reactivity of HOOH 2 ϩ was studied using a sector instrument (EBEB) and an FT-ICR apparatus 225. Metastable HOOH 2 ϩ ions having internal energy sufficiently close to the dissociation threshold decompose spontaneously to form H 3 O ϩ and 3 O, consistent with previous theoretical predictions that ground state singlet HOOH 2 ϩ will decompose with loss of an oxygen atom via a spin change mechanism.…”
supporting
confidence: 76%
“…Strong acids protonate the peroxide and promote a heterolytic mechanism. Indeed, experimental and computational studies indicate that protonated hydrogen peroxide, H 3 O 2 + , is a very powerful oxidant. , By contrast, weak acids such as CF 3 COOH appear to participate in the activation of H 2 O 2 in their nondissociated forms and catalyze the oxygen insertion by hydrogen bonding to the oxidant . Recently, one of us and others have demonstrated that 1-octene, which is notoriously difficult to epoxidize, undergoes epoxidation under mild conditions when H 2 O 2 is employed in fluorinated alcoholic solutions, e.g., CF 3 CH 2 OH and (CF 3 ) 2 CHOH.…”
Section: Introductionmentioning
confidence: 99%
“…In the accompanying experimental work, reactions between 18 O isotope labelled water and HOOH 2 1 were investigated using FT-ICR mass spectrometry. 3 Despite the potentially promising S N 2 mechanism, it was not possible to observe any product ion incorporating 18 O. Instead the proton transfer (reaction 4) is dominating.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of protonated hydrogen peroxide has recently been the subject of several studies. [1][2][3][4] Gas phase experiments, supported by quantum chemical and reaction dynamics simulations, have demonstrated that this species is a strong oxidant, and that the mechanism of action is by hydride abstraction from the substrate molecule, as in the reaction with ethane:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation